Development of Socioscientific Issue-Based Interactive E-Modules to Improve Students Critical Thinking Skills on Global Warming Issues - Ummul Uslima; Sunyono Sunyono; Dewi Lengkana (Jurnal Pendidikan MIPA, 2023)
This development research aims to develop and validate interactive e-modules based on socio scientific issues on Global Warming material to improve students' critical thinking skills. This study uses the Research and Development method with 4D design (Define, Design, Develop, Disseminate). The results of construct validation get a score of 85.3 and the feasibility of the material gets a score of 88.2 with the final conclusion "feasible to use with improvement". As well as the Practicality Test from student responses, an average score of 93.25 is in the very high category and the responses from the teachers get a score of 89.8 in the very high category. Based on the pre-test and post-test when the trials were carried out on students, the N-gain value was obtained in the experimental class of 83.91 which means effective and the control class 54.31 which means less effective. Overall, the research findings show that the developed e-module is validated in a very valid category and can improve students' critical thinking skills.Keywords: interactive e-modules, socio scientific issues, critical thinking skills.DOI: http://dx.doi.org/10.23960/jpmipa/v24i1.pp324-334